Problematic issues of Ukrainian unofficial anthroponymic names classification - Vilchynska, Tetiana; Sokol, Mariana; Bachynska, Halyna; Verbovetska, Oksana; Svystun, Nina; Shton, Olena (Universidade Estadual Paulista, 2021)
The article considers the problems related to modern Ukrainian informal names of people, particularly their status, classification, etc. The study is aimed to research how informal anthroponyms are interpreted in modern onomastics, define the scope of the term "nickname," and find out the status of informal onyms that do not show clear signs of a particular class. Description and classification have been the main research methods. Ithas been confirmed that the understanding of «nickname» concept implies either the whole set of informal names or one of the groups of colloquial ones. It has been established that the differences in the classification of informal names are because many classes occupy an intermediate place and have features of both categories. The study has been shown that informal names in the Ukrainian anthroponymicon need further thorough research.